Inhibition of p53 acetylation by INHAT subunit SET/TAF-I? represses p53 activity. - Kim, J.Y.; Lee, K.S.; Seol, J.E.; Yu, K.; Chakravarti, D.; Seo, S.B. (Nucleic Acids Research, 2012)
The tumor suppressor p53 responds to a wide variety of cellular stress signals. Among potential regulatory pathways, post-translational modifications such as acetylation by CBP/p300 and PCAF have been suggested for modulation of p53 activity. However, exactly how p53 acetylation is modulated remains poorly understood. Here, we found that SET/TAF-I? inhibited p300- and PCAF-mediated p53 acetylation in an INHAT (inhibitor of histone acetyltransferase) domain-dependent manner. SET/TAF-I? interacted with p53 and repressed transcription of p53 target genes. Consequently, SET/TAF-I? blocked both p53-mediated cell cycle arrest and apoptosis in response to cellular stress. Using different apoptosis analyses, including FACS, TUNEL and BrdU incorporation assays, we also found that SET/TAF-I? induced cellular proliferation via inhibition of p53 acetylation. Furthermore, we observed that apoptotic Drosophila eye phenotype induced by either dp53 overexpression or UV irradiation was rescued by expression of dSet. Inhibition of dp53 acetylation by dSet was observed in both cases. Our findings provide new insights into the regulation of stress-induced p53 activation by HAT-inhibiting histone chaperone SET/TAF-I?.